Food Insecurity and Healthy Behavior Counseling in Primary Care - Nederveld, Andrea (J Health Dispar Res Pract, 2018)
OBJECTIVE: While food insecurity (FI) has been associated with obesity in some studies, few have examined the relationship between FI and health attitudes and behaviors. We hypothesized that families who experienced FI would report lower importance of discussing health-related behavior change, report lower physical activity (PA) and have children who were more likely to be obese. DESIGN/METHODS: We conducted a cross-sectional analysis of data collected from 2012 - 2015 from three clinics serving primarily low-income, Latino patients. Parents of 6 to 12 year old children presenting for well child care were surveyed about their experience of food insecurity, the importance of discussing behavior change with a health care provider and their children’s physical activity. We calculated children’s BMI z scores from the height and weight measured at that visit. We used path analysis to test our hypotheses. RESULTS: Among 1048 families in the study sample, 610 reported experiencing FI (56%). Experiencing FI was positively related to importance of discussing health behavior (p < 0.001) and negatively related to PA (p=0.008). The relationship between FI and BMI was not significant. CONCLUSION: We found FI was associated with greater perceived importance of discussing health related behavior change, but lower amounts of PA, indicating contrasting attitudes and behaviors. Families facing food insecurity are likely experiencing financial and other barriers to PA, as evidenced by lower reported PA. Providers counseling low-income populations should not presume that food insecure families are unwilling to discuss weight related health behavior changes.